Stomach perforation as a complication of non-diagnosed pyloric atresia type I - Silke Steiner; Ammar Alazki; Steffan Loff (Elsevier, 2022)
Pyloric atresia is a rare malformation with severe complications, if the diagnosis is delayed. We report the case of a 5 day old girl who required an emergency operation because of stomach perforation due to pyloric atresia type I. The assosciation of PA with Epidermyolisis bullosa is well described and early imaging as ultrasound and x-ray to exclude pyloric atresia is recommended in children with suspect skin or hereditary predisposition. Otherwise healthy neonates with pyloric atresia run the risk that the sufficient surgical therapy is initiated when complications already appeared. We recommend immediate diagnostic steps to avoid life-threatening consequences when newborns show symptoms of upper gastrointestinal tract obstruction in the first hours of life.